Peran Kegiatan Ekstrakulikuler Dalam Mengembangkan Karir Siswa Pada Sekolah Kebangsaan Bandar Puteri Jaya Sungai Petani Kedah, Malaysia - Febriani, Melisa; Hasibuan, Ali Daud (Jayapangus Press, 2025)
Extracurricular activities play a crucial role in developing students' career preparation at the elementary school level. This study examined the role of extracurricular activities in developing students' careers at Bandar Puteri Jaya National School, Malaysia, with support from parents, teachers, environment, and school facilities. The research aimed to analyze the role of extracurricular activities in developing students' careers by comparing Malaysian and Indonesian schools. This qualitative study employed descriptive methods including interviews, observations, and documentation. Data were collected from guidance counselors and analyzed through data reduction, display, and conclusion drawing. The findings revealed that extracurricular activities in both Malaysia and Indonesia share similarities and differences in implementation approaches. In Malaysia, the school offers diverse activities including sports (football, basketball, handball), dance, arts, marching band, and music with systematic scheduling and comprehensive facilities. Indonesian schools focus primarily on scouting activities due to resource limitations. Both schools demonstrate that extracurricular activities effectively develop students' potential, interests, and talents while building essential character traits such as teamwork, leadership, discipline, and responsibility. The study concludes that extracurricular activities serve as vital platforms for career preparation, enabling students to explore their capabilities and develop skills necessary for future educational and career advancement.